Estudio económico del cultivo de maíz (Zea mays L) en el recinto Concepción del cantón Baba - Fuentes Carriel, Freddy Fabricio (2019)
This research work was carried out in the Concepción Campus of the Guare parish, Baba canton, Los Ríos Province, in which a survey was carried out on the farmers of this sector to know if they carry out an economic study when conducting a crop, which stated that there are few who perform an economic study others do not do it because they are unaware of it, due to lack of information. Farmers do not obtain a profitable return on their corn crop, some rent land or have a small area, so their expenses are usually greater than or equal to income, they also mention that there is no fair price in the market and that intermediaries They pay well below the set price.